Exosomes as a New Delivery Vehicle in Inflammatory Bowel Disease - Xiaomei Wang; Guoliang Zhou; Wanwan Zhou; Xin Wang; Xiao Wang; Chenggui Miao (MDPI AG, 2021)
Inflammatory bowel disease (IBD) is a type of chronic relapsing inflammatory disease. The pathogenesis of IBD is still unclear, which may involve environmental factors, genetic factors, intestinal microbiota disorder, and abnormal immune responses. Exosomes (30-150 nm) are found in various body fluids, including blood, saliva, urine, and cerebrospinal fluid. Exosomes mediate intercellular communication and regulate cell biological activity by carrying non-coding RNAs, proteins, and lipids. There is evidence that exosomes are involved in the pathogenesis of IBD. In view of the important roles of exosomes in the pathogenesis of IBD, this work systematically reviews the latest research progress of exosomes in IBD, especially the roles of exosomes as non-coding RNA delivery systems in the pathogenesis of IBD, including a disordered immune response, barrier function, and intestinal microbiota. The review will help to clarify the pathogenesis of IBD and explore new diagnostic markers and therapeutic targets for patients with IBD.